Giant multinodular infantile fibrosarcoma: a case report - Usman, Aliyu M.; Ehiosa, Okuofo C.; Charles, Okwonna O.; Adamu, Abdullahi (International Journal of Research in Medical Sciences, 2018)
Infantile fibrosarcoma is a rare type of soft tissue sarcoma seen in children usually less than 2years of age. Few cases of giant infantile fibrosarcoma have been reported in literature. We report a rare case of a giant multi-nodular infantile fibrosarcoma in the left anterolateral chest wall in a 7-year-old boy. The tumour was said to have been recurrent twice for about 6 years. At presentation patient was evaluated and was commenced on 6 cycles of neoadjuvant chemotherapy with vincristine, adriamycin and cyclophosphamide (VAC) regimen to alternate with Ifosfamide/Etoposide (IE) regimen with very good response. Thereafter, had a wide local excision of the tumour and then had 4 more cycles of adjuvant chemotherapy. His 6months follow up showed no evidence of tumour recurrence. Infantile fibrosarcoma is said to be chemo-sensitive tumour with very good response, though surgical excision is the main treatment of choice and overall it is said to have a good prognosis.